If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8x+x=14
We simplify the equation to the form, which is simple to understand
-8x+x=14
We move all terms containing x to the left and all other terms to the right.
-8x+1x=+14
We simplify left and right side of the equation.
-7x=+14
We divide both sides of the equation by -7 to get x.
x=-2
| 1/3(3.14)(36)(4) | | 8-5w=-23 | | 3.8w+3.2=2.4(w+4) | | 15=6m-3 | | (1/2)x=(9/14)x+(1/7) | | 6-7x=-5x-18 | | 6x+3=p | | (x*x)=5/2 | | z/3=-1/6 | | -9x+8=3x-16 | | 9x-4x+136=9x+80 | | 8(8n-4)-1=-289 | | 7m-50+3m=100+8m | | 9x-4x+136=9x+180 | | 45=9 | | x/3=-1/6 | | b-4.7=2.1 | | 3-r=2 | | -1=-8+x/8 | | 4x-2=-2x+22 | | z^3+4=z^2+4z | | 25=9 | | z^3+4=z | | F(x)=5x^2-10x-4 | | 7x+18-6x=-8-12 | | 1/27h=28 | | 4i+6=-1-4 | | 18x+-5=3(6x+-2) | | 16=9 | | (7y-1)=(11y+19) | | 2x^3-12x^2+18x=0 | | (x+7)(x-6)=(x+7) |